Evaluation of a Brief Mindfulness Strategy in the Classroom: A Feasibility Study (International Journal of Nursing Education, 2020)
Purpose: The purpose of this quality improvement pilot project was to evaluate preliminary outcomes andstudent acceptance of integrating a brief mindfulness strategy in the classroom of a required pre-licensurenursing course.Method: A one-group pre- and post-test design was used to pilot a brief mindfulness strategy with prelicensure nursing students during the last six weeks of the term. Outcome measures included anxiety,depression, and perceived stress. Participation in data collection activities was voluntary. Data were collectedat the beginning (T1), middle (T2), and end of the 14-week term (T3). A focus group was conducted togather student acceptance data at the end of the project.Findings: There was no significant change in outcome measures over time. Recommendations includedintroduction of mindfulness early in the prelicensure nursing program, integration of a variety of activities,and making mindfulness an optional in-class activity.Conclusion: Mindfulness practices introduced early in pre-licensure programs may assist students withadoption of strategies to regulate anxiety, depression and perceived stress.
Keywords: Mindfulness, mindfulness intervention, anxiety, depression, stress.